2022
DOI: 10.1108/ijchm-05-2021-0551
|View full text |Cite
|
Sign up to set email alerts
|

Women in hospitality and tourism: a study of the top-down and bottom-up dynamics

Abstract: Purpose This study aims to investigate the impact of women’s representation at one hierarchical level on women’s representation above or below that level. No past research investigated these effects in the hospitality and tourism industries. The mixed results of research in other industries and across industries demand tests of curvilinearity and moderators. Design/methodology/approach Using annual equality reports, a panel data set for 2010–2019 was created for the hospitality and tourism industries. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 60 publications
2
20
0
1
Order By: Relevance
“…While gender diversity enhances CSR, boards need a certain number of women to experience the true benefits of gender diversity. This supports the existing argument on the number of women directors on board (Ali et al, 2022; Yang et al, 2019; Yarram & Adapa, 2021). Most of the female participants (80%) and three male participants raised the issue that if boards do not reach a certain level of gender diversity, the insignificant presence of women directors may not impact decision‐making.…”
Section: Discussionsupporting
confidence: 89%
“…While gender diversity enhances CSR, boards need a certain number of women to experience the true benefits of gender diversity. This supports the existing argument on the number of women directors on board (Ali et al, 2022; Yang et al, 2019; Yarram & Adapa, 2021). Most of the female participants (80%) and three male participants raised the issue that if boards do not reach a certain level of gender diversity, the insignificant presence of women directors may not impact decision‐making.…”
Section: Discussionsupporting
confidence: 89%
“…).” However, women are facing more challenges in work station rather than men (Hutchings et al , 2020; Santero-Sanchez et al , 2015). This has been demonstrated by several studies that women’s participation in managerial positions is disappointedly low in tourism industry (Ali et al , 2022; Pinar et al , 2011) even research has proven that both male and women are capable of managing businesses successfully (Marco-Lajara and Úbeda-García, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the past three decades, tourism and gender studies have grown significantly (Alarc on and Cole, 2019;Ali et al, 2022;Baum, 2013;Engelhardt and Prskawetz, 2004;Gurrieri et al, 2014;Harvey et al, 1995;Okumus et al, 2010;Swain, 1993). Previous studies mainly concentrated on variations in women's education, employment and income with the expansion of tourism and mentioned the positive status of women in the community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, while women make up 51.9% of the hospitality workforce and 61% of the H&T tourism industry, women on the board of directors in these sectors are only 23% (Equality in Tourism International 2018; MBS Intelligence 2021; UNWTO 2019). Recent research has also suggested that women in the H&T sector still experience more barriers and disadvantages compared to their male counterparts (Ali, Grabarski, and Konrad 2022; Baum et al 2020; Gebbels, Gao, and Cai 2020; Mooney 2020). As such, although significant progress in relation to gender diversity has been achieved since 2015, within the H&T sector, there is as yet substantial room for further improvement (Russen, Dawson, and Madera 2021).…”
Section: Introductionmentioning
confidence: 99%